CHIRAQCHI FORT DURING THE BUKHARA EMPIRE - Sabohat Abduraimova (Web of Journals Publishing, 2024)
In the 18th - 20th centuries, Chirakchi was one of the major strongholds of Bukhara, which included more than a hundred villages. One of the princes stayed in this city. That is, the sons of the emirs of Bukhara were in charge of this land with the title of "bek". This article provides information about the territory, population and social structure of the Chirakchi district within the Bukhara Emirate, as well as the influence of political processes in the emirate on the district.
Keywords: Kashkadarya, Chirakchi, Chirakchi city, Shahrisabz historical region, Timurids, Shaibanis, Bukhara, Bukhara Khanate, Bukhara Emirate, Beklik, Mangit dynasty.